2017
DOI: 10.1002/hep.29291
|View full text |Cite
|
Sign up to set email alerts
|

Serum extracellular vesicles contain protein biomarkers for primary sclerosing cholangitis and cholangiocarcinoma

Abstract: Proteomic signatures found in serum EV of CCA, PSC, and HCC patients show potential usefulness as diagnostic tools. (Hepatology 2017;66:1125-1143).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 43 publications
6
195
1
Order By: Relevance
“…A panel of miRNAs isolated from EVs in bile had a reported sensitivity of 67% and a specificity of 96% for the diagnosis of cholangiocarcinoma 60 . Furthermore, a separate proteomic analysis indicated that greater levels of oncogenic proteins are present in EVs obtained from cultures of human cholangiocarcinoma cells versus those derived from nonmalignant human cholangiocytes 61 . In addition, Severino et al 62 demonstrated that patients with malignant biliary strictures have a significantly higher concentration of EVs in bile than those with nonmalignant strictures (2.4 × 10 15 versus 1.6 × 10 14 nanoparticles/l in the discovery cohort, P <0.0001; 4.0 × 10 15 versus 1.3 × 10 14 nanoparticles/l in the verification cohort, P <0.0001).…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…A panel of miRNAs isolated from EVs in bile had a reported sensitivity of 67% and a specificity of 96% for the diagnosis of cholangiocarcinoma 60 . Furthermore, a separate proteomic analysis indicated that greater levels of oncogenic proteins are present in EVs obtained from cultures of human cholangiocarcinoma cells versus those derived from nonmalignant human cholangiocytes 61 . In addition, Severino et al 62 demonstrated that patients with malignant biliary strictures have a significantly higher concentration of EVs in bile than those with nonmalignant strictures (2.4 × 10 15 versus 1.6 × 10 14 nanoparticles/l in the discovery cohort, P <0.0001; 4.0 × 10 15 versus 1.3 × 10 14 nanoparticles/l in the verification cohort, P <0.0001).…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…Proteins within serum EVs were also found to be excellent biomarkers, able to differentiate between patients with primary sclerosing cholangitis (PSC) and those with CCA or HCC, as well as normal liver controls . Because PSC is the most important risk factor for perihilar CCA in the United States and because, clinically, it is often difficult to differentiate between a nonmalignant stricture in PSC and frank CCA, the differentiation between PSC and CCA was of utmost importance.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…90 Recently, a study screening for noninvasive biomarkers for diagnosis of primary sclerosing cholangitis (PSC), CCA, and HCC, identified several proteins that are specifically enriched in serum-derived EVs, including aminopeptidase N (AMPN), gamma-glutamyltransferase 1(GGT1), polymeric immunoglobulin receptor (PIGR), vanin 1 (VNN1), immunoglobulin heavy constant alpha 1 (IGHA1), C-reactive protein (CRP), alpha-1-acid glycoprotein 1 (A1AG1), and alectin-3-binding protein (LG3BP). 91 …”
Section: Evs As Potential Biomarkers For Liver Diseasesmentioning
confidence: 99%